Thermal control stable polyurethane plugging material and formula determination method thereof
By incorporating a specific proportion of inorganic hydrated salts and fly ash into polyurethane, the problem of heat accumulation and insufficient thermal stability of polyurethane materials during the underground curing process is solved, achieving efficient cooling and improved thermal stability of the material, and is suitable for Coal mine underground environment.
Patent Information
- Application Number
- CN202411185423.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-27
- Publication Date
- 2025-01-21
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The large amount of heat released by polyurethane materials during the downhole grouting and curing process leads to the accumulation of downhole heat, increasing the risk of coal spontaneous combustion. At the same time, its thermal stability is insufficient, prone to thermal degradation, and may release toxic and harmful gases.
By incorporating 16% MgSO4·7H2O, 12% Na2CO3·10H2O and 50% fly ash into polyurethane, the synergistic effect of inorganic hydrated salts and fly ash is used to reduce the heat release during the curing process and improve the thermal stability of the material. sex.
It significantly reduces the heat released during the polyurethane curing process, avoids the risk of underground heat accumulation and coal spontaneous combustion, and enhances the stability and thermal stability of the material, making it suitable for underground coal mine environments.
Smart Images

Figure CN119331407A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of underground coal mine plugging materials and relates to a thermally controlled stable polyurethane plugging material and a method for determining a formula thereof. Background Art
[0002] During the coal mining process, mine air leakage will cause air leakage in goafs, air intake and return tunnels, stopped mining lines and open cutting eyes, closed tunnels with floating coal, and crushed coal pillars, causing coal oxidation and inducing mine fire accidents. Therefore, measures and methods must be taken to control air leakage and prevent risks.
[0003] Due to its unique pore structure and excellent closed-cell rate, polyurethane materials have shown significant plugging effects in the field of coal mine air leakage plugging and have become one of the most widely used plugging materials. However, the large amount of heat released by polyurethane materials during the underground grouting and curing process, coupled with its own poor thermal conductivity, can easily lead to heat accumulation underground and increase the risk of coal spontaneous combustion. In addition, polyurethane has insufficient thermal stability and is prone to thermal degradation in high-temperature environments. The isocyanate and rich C and H elements in its components make the material flammable and may release toxic and harmful gases. Although the reaction temperature of existing mining polyurethane materials is limited, there are still potential fire hazards, which limits its large-scale application.
[0004] To solve the above problems, inorganic salt hydrates have become ideal additive candidates due to their phase change endothermic effect, a wide variety, abundant reserves, low cost, and environmental protection. Introducing it into the polyurethane system can not only effectively reduce the heat release during the curing reaction, but also bring significant advantages in cost control and environmental protection. At the same time, fly ash, as a by-product of the coal-fired industry, has a huge output and will cause multiple pollution to the environment if improperly handled. However, fly ash is also a potential resource treasure house. Through reasonable development and utilization, it can not only reduce the consumption of natural resources, promote the resource utilization of coal-based solid waste, but also effectively alleviate the environmental problems caused by fly ash accumulation. Fly ash is rich in resources and low in price, which provides the possibility of reducing production costs and further enhances the economic feasibility of the material. However, as mentioned above, there are many types of inorganic salt hydrates. How to determine which inorganic salt hydrate to use for doping is a heavy task. Using conventional test methods, it is difficult to quickly find the best formula and the best ratio of each component, with poor accuracy and low efficiency. Summary of the invention
[0005] The present invention overcomes the shortcomings of the prior art and proposes a thermally stable polyurethane plugging material and a method for determining its formula. The invention solves the problems of insufficient thermal stability and high heat release during the curing process of polyurethane, and the problems of poor accuracy and low efficiency in finding the best formula and the best ratio of each component using conventional test methods for thermally stable polyurethane plugging materials.
[0006] In order to achieve the above object, the present invention is implemented through the following technical solutions.
[0007] A thermally controlled stable polyurethane plugging material is composed of the following raw materials in mass fractions: 14% to 18% of MgSO4·7H2O, 10% to 14% of Na2CO3·10H2O, 45% to 55% of fly ash, and the remainder being polyurethane; the polyurethane is a mixture of polyurethane black material and polyurethane white material; the mass fraction refers to the percentage content of the component in the polyurethane white material.
[0008] Preferably, it is composed of the following raw materials in mass fractions: 16% MgSO4·7H2O, 12% Na2CO3·10H2O, 50% fly ash, and the rest is polyurethane.
[0009] More preferably, the polyurethane is a mixture of polyurethane black material and polyurethane white material in a volume ratio of 1:1.
[0010] The method for determining the formula of a thermally stable polyurethane plugging material comprises the following steps: S1: Conduct temperature measurement experiments on a single hydrated salt doped polyurethane system to determine the cooling effect of different types of hydrated salts doped into the polyurethane system, and select two hydrated salt materials with better cooling effect based on the experimental results; S2: The selected hydrated salt materials are orthogonally designed and compounded into polyurethane, and the curing temperature of the composite system under different doping ratios is measured and the glass transition temperature and diffusion coefficient of each composite system are calculated by molecular dynamics simulation. Based on the analysis of the results, the hydrated salt doping formula is obtained; S3: On the basis of step S2, fly ash of different mass fractions is continued to be doped, and the optimal formula of the modified polyurethane material of hydrated salt and fly ash is obtained by measuring the curing temperature of the composite system and simulating and calculating the glass transition temperature and diffusion coefficient of the composite system.
[0011] Preferably, the temperature measurement experiment is to add hydrated salt to polyurethane and stir it. When the slurry appears milky white, the slurry is quickly poured into a mold for curing reaction; during the slurry curing process, a thermometer is inserted into the center of the stirred and evenly mixed slurry, and the temperature of the sample is recorded. The recording is stopped when the temperature stops rising, which is the highest reaction temperature of the slurry curing.
[0012] Preferably, the simulation calculation of the glass transition temperature comprises the following steps: Step 1: Establishing a composite model: For the glass transition temperature in step S2, a composite model of pure polyurethane and polyurethane doped with hydrated salts of different mass fractions is established; for the glass transition temperature in step S3, a composite model of polyurethane doped with hydrated salts and fly ash of different mass fractions is established; Step 2: Perform geometric optimization on all models; perform annealing cycles of 200ps, 500ps and 200ps on all models in canonical ensemble NVT, isothermal and isobaric ensemble NPT and canonical ensemble NVT respectively; Step 3: After the pretreatment process, the microscopic dynamic equilibrium process at nine temperatures of 500K, 450K, 400K, 350K, 300K, 250K, 200K, 150K, and 100K was simulated under the NPT ensemble for the pure polyurethane model and the polyurethane model doped with different mass fractions of inorganic salts. In each stage, the final conformation of the previous temperature point was used as the initial conformation of the next temperature point. Step 3: Verify the rationality of the constructed model through energy, density, solubility parameter, and radial distribution function; Step 4: Obtain the glass transition temperature of each composite system model through the specific volume-temperature relationship method. After the model kinetic simulation is completed, extract the average value of the model density at each temperature, and then use the reciprocal of the density, i.e., the specific volume, as the ordinate and the corresponding temperature point as the abscissa to obtain the specific volume-temperature relationship curve. Then perform linear fitting on the curve to obtain the inflection point of the curve, which is the Tg value of the system model.
[0013] Preferably, the steps for calculating the diffusion coefficient are: repeating the steps 1 to 3 of simulating and calculating the glass transition temperature; then calculating the mean square displacement curve of each system; and calculating the diffusion coefficient through the slope of MSD according to the Einstein equation.
[0014] The beneficial effects of the present invention compared with the prior art are as follows: The present invention adds 16% MgSO4·7H2O+12% Na2CO3·10H2O+50% fly ash to polyurethane (PU) white material. Inorganic hydrated salt and fly ash produce a good synergistic effect at this specific doping ratio, significantly improving the comprehensive performance of PU materials. They not only effectively reduce the heat release during the curing process of polyurethane, avoid the risk of underground heat accumulation and coal spontaneous combustion, but also greatly enhance the stability and thermal stability of the material. This allows polyurethane materials to be widely used in environments such as underground coal mines, providing a solid guarantee for coal safety production, while promoting the development of coal-based solid waste resource utilization technology, and achieving a win-win situation of economic benefits and environmental protection.
[0015] The invention dopes two hydrated salts into a polyurethane system in orthogonal proportions, measures the curing temperature of the composite system, and calculates the glass transition temperature and diffusion coefficient of each composite system by molecular dynamics simulation, thereby analyzing and obtaining a hydrated salt doping formula with better modification effect; then, fly ash is further doped into the polyurethane system on the basis of the hydrated salt doping formula, measures the curing temperature of the composite system, and simulates and calculates the glass transition temperature and diffusion coefficient of the composite system, thereby obtaining an optimal formula of a polyurethane material modified by compounding hydrated salt and fly ash; the method can accurately and quickly determine the optimal formula and the optimal ratio of each component, thereby effectively improving the accuracy and efficiency of formula determination. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 Multiple composite model diagrams representing the orthogonal complex doping of two hydrated salts into PU system; Figure 2 These are some sample pictures of modified polyurethane plugging materials. DETAILED DESCRIPTION
[0017] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention clearer, the present invention is further described in detail in conjunction with the embodiments and the accompanying drawings. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. The technical solutions of the present invention are described in detail below in conjunction with the embodiments and the accompanying drawings, but the scope of protection is not limited thereto.
[0018] This embodiment provides a thermally stable polyurethane plugging material and a method for determining its formula, and the specific steps are as follows: Step 1: Determine the cooling effect of different types of single hydrated salt doped polyurethane systems In this experiment, the highest temperature during the curing reaction of the material is used to evaluate the heat released by the reaction during the solidification of the polyurethane plugging material. The mass fractions in this embodiment are the fractions of the added substances to the mass of the polyurethane white material.
[0019] 1.1. Temperature measurement experiment during the curing process of pure polyurethane material (1) Use a measuring cylinder to measure the same volume of polyurethane black material and white material, and then mix and stir evenly in a volume ratio of 1:1 between black and white materials; (2) When the slurry appears milky white, quickly pour it into the mold for curing reaction; (3) During the slurry solidification process, insert the thermometer into the center of the stirred and mixed reaction liquid, record the temperature of the sample, and stop recording when the temperature stops rising. This is the highest reaction temperature of the sample solidification. When conducting the temperature measurement experiment, it is necessary to repeat it three times at room temperature (23±1)℃, record the highest temperature of each experiment, and take the average of the three experiments as the final solidification temperature.
[0020] 1.2. Temperature measurement experiment of single hydrated salt doped polyurethane system (1) Use an electronic analytical balance to weigh 10% by mass of magnesium sulfate heptahydrate, sodium carbonate decahydrate, sodium sulfate decahydrate, calcium chloride hexahydrate, and calcium sulfate dihydrate; in preliminary exploratory studies, 10% is a starting point to determine the basic trend and effect of hydrated salt doping on the curing temperature of the polyurethane system.
[0021] (2) Add the hydrated salt in (1) to the polyurethane white material, use a magnetic stirrer to fully mix the hydrated salt and the white material and stir them evenly to perform doping, and then mix and react with the black material; (3) Repeat steps (2) and (3) in 1.1 to carry out temperature measurement experiments on a single hydrated salt-doped polyurethane system.
[0022] 1.3 Results Analysis After the temperature measurement experiment, the highest reaction temperatures of the pure polyurethane system and the system doped with a single hydrated salt can be obtained, as shown in Table 1, where PU stands for polyurethane.
[0023] As shown in Table 1, after adding hydrated salts to polyurethane, the curing temperature of the system is reduced due to the phase change of the hydrated salts for dehydration and heat absorption. After adding magnesium sulfate heptahydrate to the system, the curing temperature of the system can be reduced to 84.6°C, a decrease of 8.03°C. After adding sodium carbonate decahydrate, the maximum curing temperature of the system can be reduced to 85.53°C, a decrease of 7.1°C. Compared with the other three materials, magnesium sulfate heptahydrate and sodium carbonate decahydrate are added to the system, which has a better cooling effect on the reaction. Therefore, the following compounding experiments and simulation calculations are based on these two hydrated salts.
[0024] Step 2: Determine the modification effect of the two hydrated salt materials on the performance of polyurethane 2.1. Temperature measurement experiment of two hydrated salt materials mixed with polyurethane (1) According to the experimental results in step 1, two materials with better cooling effect are selected from the above five inorganic hydrated salt materials, namely MgSO4·7H2O and Na2CO3·10H2O, and the cooling effect is studied.
[0025] (2) The two selected hydrated salt materials were subjected to orthogonal compounding experiments with mass fractions of 4%, 8%, 12%, and 16%, respectively. The orthogonal experimental design is shown in Table 2, where ① is MgSO4·7H2O and ② is Na2CO3·10H2O. According to the design scheme in the orthogonal experimental table, group compounding doping temperature measurement experiments were carried out.
[0026] (3) Use an electronic analytical balance to weigh the corresponding mass fraction of hydrated salt in each experiment; (4) Using a magnetic stirrer, fully stir and add the two hydrated salts of different mass fractions into the polyurethane white material, and then mix them evenly with the black material; (5) When the slurry appears milky white, quickly pour it into the mold for curing reaction; (6) During the slurry solidification process, insert the thermometer into the center of the stirred and mixed reaction liquid, record the temperature of the sample, and stop recording when the temperature stops rising. This is the highest reaction temperature of the sample solidification.
[0027] 2.2. Simulation calculation of the glass transition temperature of two hydrated salt materials mixed and doped into the polyurethane system The glass transition temperature can indicate the thermal stability of the material. The higher the glass transition temperature, the better the thermal stability of the material. According to the model requirements, taking into account the actual situation, simulation parameters and simulation time, this embodiment uses Materialsstudio 2019 software for simulation calculation: (1) The composite models of pure polyurethane and polyurethane doped with different mass fractions of MgSO4·7H2O and Na2CO3·10H2O in the orthogonal experimental table were established. The composite models of PU after orthogonal doping of hydrated salt are shown in the figure below. Figure 1 As shown; (2) Perform 10,000 steps of geometry optimization on all the above models; (3) All the above models were subjected to 200ps, 500ps and 200ps annealing cycles in the canonical ensemble (NVT), isothermal and isobaric ensemble (NPT) and canonical ensemble (NVT) respectively. In the annealing step, the system temperature was increased from 250K to 500K, and then cooled to 250K, and the cycle was repeated 5 times; (4) After the pretreatment process, the pure PU model and the PU model doped with different mass fractions of inorganic salts were used as the objects, and their microscopic dynamic equilibrium processes at nine temperatures of 500K, 450K, 400K, 350K, 300K, 250K, 200K, 150K, and 100K were simulated under the NPT ensemble. In each stage, the final conformation of the previous temperature point (high temperature) was used as the initial conformation of the next temperature point (low temperature); (5) Verify the rationality of the constructed model through index parameters such as energy, density, solubility parameter, radial distribution function, etc.; (6) The glass transition temperature of each composite system model is obtained by the specific volume-temperature relationship method. After the model kinetic simulation is completed, the average value of the model density at each temperature is extracted. Then, the reciprocal of the density, i.e., the specific volume, is used as the ordinate, and the corresponding temperature point is used as the abscissa to obtain the specific volume-temperature relationship curve. The curve is then linearly fitted to obtain the inflection point of the curve, which is the Tg value of the system model.
[0028] 2.3. Calculation of the diffusion coefficient of the polyurethane system doped with two hydrated salt materials (1) Repeat steps (1) to (5) in 2.2. (2) Calculate the mean square displacement curve of each system using the Forcite-Analysis function in the software; (3) According to the Einstein equation, the diffusion coefficient is calculated by the slope of the MSD. The Einstein equation is as follows: , where N represents the number of atoms diffused. Because the simulation time is long enough and the a of N molecules has been simulated during the simulation MSD An average operation is performed, so the equation can be simplified according to the MSD formula as follows: , K MSD It is expressed as the slope obtained by the least square linear fitting of the molecular mean square displacement curve. That is, the diffusion coefficient can be approximated to 1 / 6 of the MSD slope. The diffusion coefficient of each composite simulation system is calculated according to this method.
[0029] The diffusion coefficient can indicate the stability of a material. The larger the diffusion coefficient, the more violent the molecular motion and the worse the stability of the molecular structure. On the contrary, when the diffusion coefficient is smaller, the molecules encounter greater resistance and restraining force when moving in the medium, the molecular motion will slow down, and the stability of the molecular structure will improve.
[0030] 2.4 Results Analysis By adding different mass fractions of MgSO4·7H2O and Na2CO3·10H2O into pure polyurethane, an orthogonal experimental design was carried out to study the effect of hydrated salt composite doping. The maximum reaction temperature of the composite polyurethane system after doping was measured, and the glass transition temperature and diffusion coefficient of the composite system after doping were calculated by simulation. The experimental results are shown in Table 3, where ① is MgSO4·7H2O, ② is Na2CO3·10H2O, and PU is polyurethane.
[0031] As shown in Table 3, after MgSO4·7H2O and Na2CO3·10H2O were mixed and doped into the PU system, the curing temperature of all composite systems was reduced, which improved the safety of the materials. Among them, the 8th, 12th, 16th, and 15th groups had a larger cooling range and better effect; the glass transition temperature of all composite systems also increased to varying degrees compared with the pure PU system, which improved the thermal stability of the materials. Among them, the 15th, 14th, 13th, and 16th groups had a larger increase and better effect; the larger the diffusion coefficient, the more violent the molecular movement, and the worse the stability of the molecular structure. On the contrary, when the diffusion coefficient is small, the molecules will encounter greater resistance when moving in the medium, the restraining force will be large, the molecular movement will slow down, and the stability of the molecular structure will be improved. Among them, after doping with hydrated salts, the diffusion coefficients of the 3rd, 2nd, 9th, and 15th groups are small, and the material stability is good.
[0032] In summary, the 15th experimental scheme, i.e., the PU+16%①+12%② composite system, has better comprehensive performance, so the following experimental simulation will continue the research on this basis.
[0033] Step 3: Determine the effect of adding fly ash on the performance of polyurethane on the basis of hydrated salt 3.1. Measurement of curing temperature of polyurethane system doped with fly ash on the basis of hydrated salt (1) Based on the optimal doping system formula selected from step 2, i.e., PU + 16% MgSO4·7H2O + 12% Na2CO3·10H2O, 10%, 20%, 30%, 40%, 50%, and 60% fly ash are further added to the polyurethane white material; (2) Use a magnetic stirrer to fully stir a certain mass fraction of hydrated salt and fly ash into the PU white material, and then mix it evenly with the black material; (3) Repeat steps (2) and (3) in step 1.1 to conduct temperature measurement experiments on the hydrated salt + fly ash composite doped PU system. (4) After the temperature measurement experiment, the finished product samples of some modified polyurethane plugging materials are shown as follows: Figure 2 shown.
[0034] 3.2. Calculate the glass transition temperature of fly ash mixed with PU + 16% MgSO4·7H2O + 12% Na2CO3·10H2O system: According to the model requirements, taking into account the actual situation, simulation parameters and simulation time, this embodiment uses Materials studio 2019 software for calculation: (1) Establish a composite model of PU + 16% MgSO4·7H2O + 12% Na2CO3·10H2O + fly ash with different mass fractions; (2) Perform 10,000 steps of geometry optimization on all the above models; (3) All the above models were subjected to 200ps, 500ps and 200ps annealing cycles in the canonical ensemble (NVT), isothermal and isobaric ensemble (NPT) and canonical ensemble (NVT) respectively. In the annealing step, the system temperature was increased from 250K to 500K, and then cooled to 250K, and the cycle was repeated 5 times; (4) After the pre-processing process, the above models are simulated in the NPT ensemble under the microscopic dynamic equilibrium process at nine temperatures: 500 K, 450 K, 400 K, 350 K, 300 K, 250 K, 200 K, 150 K, and 100 K. In each stage, the final conformation of the previous temperature point (high temperature) is used as the initial conformation of the next temperature point (low temperature); (5) Verify the rationality of the constructed model through index parameters such as energy, density, solubility parameter, radial distribution function, etc.; (6) The glass transition temperature of each composite system model is obtained by the specific volume-temperature relationship method. After the model kinetic simulation is completed, the average value of the model density at each temperature is extracted. Then, the reciprocal of the density, i.e., the specific volume, is used as the ordinate, and the corresponding temperature point is used as the abscissa to obtain the specific volume-temperature relationship curve. The curve is then linearly fitted to obtain the inflection point of the curve, which is the Tg value of the system model.
[0035] 3.3. Calculate the diffusion coefficient of fly ash mixed with PU + 16% MgSO4·7H2O + 12% Na2CO3·10H2O system: (1) Repeat (1) to (5) in 3.2; (2) Calculate the mean square displacement curve of each system through the Forcite-Analysis function; (3) The diffusion coefficient can be calculated from the slope of MSD according to the Einstein equation. The Einstein equation is as follows: , where N represents the number of atoms diffused. Because the simulation time is long enough and the a of N molecules has been simulated during the simulation MSD An average operation is performed, so the equation can be simplified according to the MSD formula as follows: , K MSD It is expressed as the slope obtained by the least square linear fitting of the molecular mean square displacement curve. That is, the diffusion coefficient can be approximated to 1 / 6 of the MSD slope. The diffusion coefficient of each composite simulation system is calculated according to this method.
[0036] 3.4 Results Analysis It can be concluded from Table 4 that after adding fly ash, the curing temperature of the composite polyurethane material is greatly reduced compared with the pure polyurethane material, and it is also reduced to varying degrees compared with the addition of hydrated salt alone. The glass transition temperature of the composite material is greatly improved compared with the pure polyurethane material, and it is also improved to a certain extent compared with the addition of hydrated salt alone; the diffusion coefficient of the composite material is greatly reduced compared with the pure polyurethane and the addition of hydrated salt alone, and the structure is more stable. From the analysis of all parameters, when the fly ash is added to the white material by 50% by mass, the curing temperature reduction level, glass transition temperature increase level, and diffusion coefficient reduction level of the entire system are in a better state. Therefore, the recommended dosage is PU+16%MgSO4·7H2O+12%Na2CO3·10H2O+50% fly ash, where the mass fractions of hydrated salt and fly ash are both the mass fractions of PU white material.
[0037] In summary, after in-depth research and optimization, the optimal formula of fly ash-based hydrated salt modified thermally controlled stable polyurethane plugging material was finally determined: 16% MgSO4·7H2O+12% Na2CO3·10H2O+50% fly ash was added to the polyurethane (PU) white material. Inorganic hydrated salt and fly ash produced a good synergistic effect at this specific doping ratio, significantly improving the comprehensive performance of PU materials. They not only effectively reduced the heat release during the curing process of polyurethane, avoided the risk of heat accumulation underground and spontaneous combustion of coal, but also greatly enhanced the stability and thermal stability of the material. This allows polyurethane materials to be widely used in coal mines and other environments, providing a solid guarantee for coal safety production, while promoting the development of coal-based solid waste resource utilization technology, and achieving a win-win situation of economic benefits and environmental protection.
[0038] The above content is a further detailed description of the present invention in combination with a specific preferred embodiment. It cannot be determined that the specific embodiments of the present invention are limited to this. For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the present invention, which should be regarded as belonging to the present invention and the scope of patent protection determined by the submitted claims.
Claims
1. A thermally stable polyurethane plugging material, characterized in that: The invention is composed of the following raw materials in mass fractions: 14% to 18% of MgSO4·7H2O, 10% to 14% of Na2CO3·10H2O, 45% to 55% of fly ash, and the rest of polyurethane; the polyurethane is a mixture of polyurethane black material and polyurethane white material; the mass fraction refers to the percentage of the component in the polyurethane white material.
2. A thermally stable polyurethane plugging material according to claim 1, characterized in that: The invention is composed of the following raw materials in mass fractions: 16% of MgSO4·7H2O, 12% of Na2CO3·10H2O, 50% of fly ash, and the rest of polyurethane.
3. A thermally stable polyurethane plugging material according to claim 2, characterized in that: The polyurethane is a mixture of polyurethane black material and polyurethane white material in a volume ratio of 1:
1.
4. A method for determining a formula of a thermally stable polyurethane plugging material according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1: Conduct temperature measurement experiments on a single hydrated salt doped polyurethane system to determine the cooling effect of different types of hydrated salts doped into the polyurethane system, and select two hydrated salt materials with better cooling effect based on the experimental results; S2: The selected hydrated salt materials are orthogonally designed and compounded into polyurethane, and the curing temperature of the composite system under different doping ratios is measured and the glass transition temperature and diffusion coefficient of each composite system are calculated by molecular dynamics simulation. Based on the analysis of the results, the hydrated salt doping formula is obtained; S3: On the basis of step S2, fly ash of different mass fractions is continued to be doped, and the optimal formula of the modified polyurethane material of hydrated salt and fly ash is obtained by measuring the curing temperature of the composite system and simulating and calculating the glass transition temperature and diffusion coefficient of the composite system.
5. The method for determining the formula of a thermally stable polyurethane plugging material according to claim 4, characterized in that: The temperature measurement experiment is to add hydrated salt to polyurethane and stir it. When the slurry appears milky white, the slurry is quickly poured into a mold for curing reaction; during the slurry curing process, a thermometer is inserted into the center of the slurry that is stirred and mixed evenly, and the temperature of the sample is recorded. The recording is stopped when the temperature stops rising, which is the highest reaction temperature of the slurry curing.
6. The method for determining the formula of a thermally stable polyurethane plugging material according to claim 4, characterized in that: The simulation calculation of glass transition temperature includes the following steps: Step 1: Establishing a composite model: For the glass transition temperature in step S2, a composite model of pure polyurethane and polyurethane doped with hydrated salts of different mass fractions is established; for the glass transition temperature in step S3, a composite model of polyurethane doped with hydrated salts and fly ash of different mass fractions is established; Step 2: Perform geometric optimization on all models; perform annealing cycles of 200ps, 500ps and 200ps on all models in canonical ensemble NVT, isothermal and isobaric ensemble NPT and canonical ensemble NVT respectively; Step 3: After the pretreatment process, the microscopic dynamic equilibrium process at nine temperatures of 500K, 450K, 400K, 350K, 300K, 250K, 200K, 150K and 100K was simulated under the NPT ensemble for the pure polyurethane model and the polyurethane model doped with different mass fractions of inorganic salts. In each stage, the final conformation of the previous temperature point was used as the initial conformation of the next temperature point. Step 3: Verify the rationality of the constructed model through energy, density, solubility parameter, and radial distribution function; Step 4: Obtain the glass transition temperature of each composite system model through the specific volume-temperature relationship method. After the model kinetic simulation is completed, extract the average value of the model density at each temperature, and then use the reciprocal of the density, i.e., the specific volume, as the ordinate and the corresponding temperature point as the abscissa to obtain the specific volume-temperature relationship curve. Then perform linear fitting on the curve to obtain the inflection point of the curve, which is the Tg value of the system model.
7. The method for determining the formula of a thermally stable polyurethane plugging material according to claim 6, characterized in that: The steps for calculating the diffusion coefficient are: repeating the steps 1 to 3 for simulating and calculating the glass transition temperature; then calculating the mean square displacement curve of each system; and calculating the diffusion coefficient through the slope of MSD according to the Einstein equation.
Citation Information
Patent Citations
Low-viscosity and high-strength epoxy resin grouting material and preparation method thereof
CN117844186A
Polyurethane composite grouting material as well as preparation method and application thereof
CN117946361A